TOWARDS AN INTEGRATIVE, COMMUNICATIVE, AND TECHNOLOGY-ENHANCED PEDAGOGY FOR TEACHING ARABIC TO NON-NATIVE SPEAKERS - Abdussalam Jabaruddin Yamjirin; Iin Maalika Vithri Achmada (International Journal of Teaching and Learning, 2025)
This study explores effective strategies for teaching Arabic to non-native speakers in the digital era through an integrative-communicative and technology-based approach. Drawing from recent empirical and theoretical studies (2023–2025), the research synthesizes three pedagogical pillars: communicative language teaching (CLT), digital transformation, and collaborative contextual learning. Findings indicate that Arabic instruction becomes more effective when teachers adopt the role of communication facilitators rather than information transmitters. The integration of gamification, blended learning, and interactive media enhances learners’ motivation, autonomy, and engagement. Additionally, contextual and collaborative approaches foster sustainable linguistic and cultural competence. This paper proposes an integrative learning model that unites communicative tasks, technological tools, and cross-cultural interaction within a learner-centered ecosystem. The study concludes that future Arabic language pedagogy must move beyond grammar-centered instruction toward a holistic paradigm that connects communication, technology, and culture to prepare learners for global intercultural competence.